HUBUNGAN POLA ASUH ORANG TUA TERHADAP KECERDASAN EMOSIONAL DI SMPN 19 DEPOK - Meysari, Ana; Annisa; Safitri, Aulia Indah; Ramadhianita, Dinda; wijaya, Ilham (UNIVERSITAS SERAMBI MEKKAH, 2024)
This research aims to analyze the relationship between parenting patterns and the emotional intelligence of class IX students at SMPN 19 Depok. The method used is correlation in this research, by collecting data from class IX students using instruments that have been tested for validity and reliability. The results of correlation analysis using SPSS 29 for Windows show that there is a significant positive relationship between parenting patterns and emotional intelligence. This means that if students have good parenting, their emotional intelligence will also be good. Conversely, if the level of parenting of a student's parents is low, then the student's emotional intelligence will also be low.